FIRST DATA ON THE CONCENTRATIONS AND DISTRIBUTION OF NOBLE METALS IN NI-CU SULFIDE ORES OF THE SOUTH MAKSUT DEPOSIT (EAST KAZAKHSTAN) - A. S. Mekhonoshin; T. B. Kolotilina; A. G. Vladimirov; Yu. V. Sokol'nikova; A. A. Doroshkov (Геодинамика и тектонофизика, 2017)
The magmatic sulfide deposits in the Central Asian orogenic belt are hosted in a series of mafic–ultramafic intrusions in the Maksut zone (E Kazakhstan), the Kalatongke and the Huangshan zones in Xinjiang (NW China) and the Hongqiling zone in NE China. In the Maksut zone there are several intrusions, the best studied from which is the South Maksut intrusion with Cu–Ni–PGE mineralization.